MANAJEMEN LALU LINTAS SATU ARAH KAWASAN TIMUR SEMARANG - Darmawan, Agus; Permana, Angga Ajie; Supriyono, Supriyono; Yulipriyono, Epf. Eko (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
East region of Semarang is a commercial area, so during rush hour in the morning, afternoon, and in the evening shows large volumes of traffic. Related to the current road which will not increase again, it shows the idea of one-way traffic management system with rotation. The development of traffic flow in the future will be much larger, with one-way traffic management, the traffic flow is expected to be spread on all of the road sections. Traffic survey was conducted on the roads and intersections on east region of Semarang. Performance analysis using the Indonesian Highway Capacity Manual (IHCM) 1997. Traffic analysis performed on existing conditions and then made several design of traffic management on Semarang region based on the traffic flow. Traffic management is being applied in the form of changes in routes, traffic load, the green time at the signalized intersection, geometric changes and additions to the road traffic facilities. From the results of the comparison that has been done, the best scenario was selected on east region of Semarang, the one-way system changes made on Ahmad Yani road to the east, Sriwijaya road to the west, MT. Haryono 2 road (near Bangkong intersection) to the north, Ki Mangunsarkoro road to the north, and the Ahmad Dahlan road to the south. To achieve one-way traffic management on east region of Semarang, the one-way traffic management plan to be implemented in stages. At the first stage, changes made on MT. Haryono 2 road (near Bangkong intersection) to the north and Katamso road to the east. In the second stage changes made on Ahmad Yani 1 road (near Simpang Lima) to the east, Ki Mangunsarkoro road to the north and Ahmad Dahlan road to the south. After the initial phase is done, The last stage can be done on Ahmad Yani 2 road (near Bangkong intersection) and Sriwijaya road to the west, so the one-way traffic management on the east region of Semarang can be implemented greatly.